Synthesis of Vibegron Enabled by a Ketoreductase Rationally Designed for High pH Dynamic Kinetic Reduction. Issue 23 (3rd May 2018) - Xu, Feng; Kosjek, Birgit; Cabirol, Fabien L.; Chen, Haibin; Desmond, Richard; Park, Jeonghan; Gohel, Anupam P.; Collier, Steven J.; Smith, Derek J.; Liu, Zhuqing; Janey, Jacob M.; Chung, John Y. L.; et al.
Abstract: Described here is an efficient stereoselective synthesis of vibegron enabled by an enzymatic dynamic kinetic reduction that proceeds in a high‐pH environment. To overcome enzyme performance limitations under these conditions, a ketoreductase was evolved by a computationally and structurally aided strategy to increase cofactor stability through tighter binding. Abstract : Evolution for synthetic efficiency : Target‐driven evolution optimizes enzymes for synthetically desired transformations under conditions that challenge and surpass known limitations of enzyme performance. A biocatalyst that was engineered for stereoselective, dynamic kinetic reduction in a high‐pH environment has enabled an efficient synthesis of vibegron, a potent β3 ‐adrenergic agonist for the treatment of overactive bladder syndrome.